The global financial crisis of 2008-2009 and the Fortune Global 500 corporations : Looking for losers among the biggest - exploratory study - Dzikowska, Marlena; Jankowska, Barbara (Economics and Business Review, 2012)
The paper focuses on the influence of the financial crisis and economic downturn during 2008-2009 on the world's 500 biggest corporations. The authors present an overview of literature providing some insight into the impact the global financial crisis and economic downturn during 2008-2009 exerted on enterprises and their operations. The empirical data gathered from the Fortune Global 500 reports during 2007-2010 are used in cluster analysis and descriptive statistics. The empirical research conducted by the authors allows to indicate that among the analyzed population there exist significant differences in terms of their financial performance measured as return on revenues, return on assets and profit per employee. The discrepancies in this area grew during the crisis period. The reaction to the crisis among the analyzed population in the first year of the crisis (which was characterized by a high level of uncertainty among enterprises), was different than in the next year (when estimation of the risk associated with ongoing activities was easier). Among the companies that were most severely influenced by the crisis (their financial performance worsened the most) dominate those operating in Airlines, Diversified Financials and Motor Vehicles and Parts industries. (original abstract)